2022
DOI: 10.1155/2022/6828657
|View full text |Cite
|
Sign up to set email alerts
|

An Extensive Comparison of the Clinical Efficiency of Acidulated Phosphate Fluoride (APF) and Neutral Sodium Fluoride (NaF) Oral Rinses in the Prevention of White Spot Lesions during Fixed Orthodontic Treatment: A Randomized Controlled Trial

Abstract: Background. The purpose of this randomized trial is to compare the efficacy of weekly once regime of neutral sodium fluoride (NaF) oral rinse with that of acidulated phosphate (APF) formulated daily mouth rinse in the reduction of white spot lesions (WSLs) associated with fixed orthodontic appliance treatment. Methods. The participants ( n = 90 ) of this single-center, two-arm p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Regarding the use of fluorinated products, mouthwashes are a very popular additional oral hygiene element [ 27 , 28 ], and in our study, a good percentage was found to use them together with a fluoride toothpaste, with high satisfaction regarding it.…”
Section: Discussionmentioning
confidence: 53%
“…Regarding the use of fluorinated products, mouthwashes are a very popular additional oral hygiene element [ 27 , 28 ], and in our study, a good percentage was found to use them together with a fluoride toothpaste, with high satisfaction regarding it.…”
Section: Discussionmentioning
confidence: 53%
“…However, budget constraints limit these methods from being used in the majority of studies. Six out of eight studies included in this review used visual evaluation and digital intraoral photographs for WSL assessment [14,16,17,[19][20][21]. These methods tend to underestimate the actual prevalence of enamel demineralization due to remains of bonding materials, moisture contamination, and blurry/overexposed pictures [14].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 8 included studies, 5 randomized controlled trials [14-18] evaluated the effects of fluorides, of which two evaluated the effect either of Ammonium F [14] or single F containing varnish [15] compared with placebo and Xylitol varnish, two included studies compared the effect between fluoride, nanosilver or CHX mouthwash [16,17], and one assessed the effect of different F containing pastes [18].…”
Section: Table 2 Data Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil penelitian ini, menunjukkan setelah dilakukan periode pengamatan selama enam bulan untuk membandingkan 1,23% APF dan 0,2% NaF untuk mencegah lesi white spot dan gingivitis mengungkapkan bahwa penggunaan APF lebih efektif dalam pencegahan white spot lesion dan gingivitis selama tahap awal perawatan ortodontik dengan peralatan cekat dan dapat dimasukkan dalam program perawatan pencegahan primer. 40 Penelitian yang dilakukan Gabriela Malts Goldenfu, et al pada tahun 2020 dengan 98 sampel yang bertujuan untuk mengetahui efektivitas 1,23% APF gel terkait oral hygiene dan instruksi diet untuk melindungi lesi kavitas non-aktif pada gigi permanen, campuran, dan sementara.…”
Section: Pembahasanunclassified